The Effect of Discipline and Leadership on Employee Performance with Motivation as Intervening Variable: The Case of Palembang City Public Works and Spatial Planning (PUPR) Office - Saputra, Darwin; Asiati, Diah Isnaini; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to determine the Influence of Discipline and Leadership on Performance through Intervening Variables of Work motivation in the Palembang City Public Works and Spatial Planning Service (PUPR) of Palembang City; this type of research is associative; this study uses variables of work motivation discipline, leadership, and performance. Sampling using the Slovin formula, with a sample use of as many as 126 respondents. The data needed is primary data with a data collection method using questionnaires. The analytical technique used in this study is the Structural Equation Model (SEM) Analysis Technique. The results showed 1) a positive but insignificant influence on discipline variables on work motivation, 2). There was a positive but not significant influence between leadership variables and work motivation variables, 3). There is a positive and significant influence between discipline variables and performance variables; 4). Leadership and performance variables have a positive and significant influence, 5). There is a positive and significant influence between work motivation and performance variables.